Exploring Speaking Anxiety Among Indonesian Arabic Language Learners: The Mediating Role of Personality Traits - Jumhana, Nana; Fachmi, Teguh; Yani, Achmad; Hassan, Lutfi (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2025)
This research investigates the determinant factors of public speaking anxiety among Indonesian university students through both pedagogical and socio-psychological lenses. Public speaking anxiety is a prevalent phenomenon in language acquisition, potentially affecting communicative competence and academic achievement, especially in the context of foreign language learning. This study explores the influence of academic motivation, intolerance of uncertainty, and the Big Five personality traits (openness, conscientiousness, agreeableness, extraversion, and neuroticism) as potential mediators in shaping speaking anxiety among Indonesian Arabic students in Islamic higher education. The research was conducted among students enrolled in Arabic Language Education programs at several state Islamic religious higher education institutions (PTKIN) in Indonesia. Structural Equation Modelling (SEM) was used to analyze the data, collected via self-report questionnaires. The results show that academic motivation does not significantly influence openness, while intolerance of uncertainty does. Of the Big Five traits, only openness and extraversion significantly affect speaking anxiety. Academic motivation influences conscientiousness, but not extraversion, while intolerance of uncertainty affects extraversion, but not agreeableness. Openness and extraversion mediate the relationship between academic motivation and speaking anxiety.